2021
DOI: 10.9758/cpn.2021.19.3.568
|View full text |Cite
|
Sign up to set email alerts
|

Lurasidone in Therapy of Treatment-resistant Ultra-rapid Cycling Bipolar Disorder: Case Report

Abstract: Lurasidone is an atypical antipsychotic approved for the treatment of schizophrenia and bipolar depression. It seems to have a favorable metabolic profile and low risk of causing adverse interactions. Here we present a case of a 25-year old female patient with treatment-resistant ultra-rapid cycling bipolar disorder, obesity, hypothyroidism, and epilepsy. Because of predominant depressive symptoms, occasional occurrence of brief psychotic symptoms and patient's somatic comorbidities, treatment with lurasidone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…He achieved clinical stability after being prescribed carbamazepine 900 mg/day and nifedipine 30 mg/day. More recently, Siwek et al 3 also documented the case of a 25-year-old woman diagnosed with ultra-RC BD. The patient had depressive episodes with anergy and marked social withdrawal interspersed with hypomanic episodes with elevated mood, tachypsychia, and increased energy levels, each lasting from a few days to 2 weeks.…”
Section: Discussionmentioning
confidence: 97%
“…He achieved clinical stability after being prescribed carbamazepine 900 mg/day and nifedipine 30 mg/day. More recently, Siwek et al 3 also documented the case of a 25-year-old woman diagnosed with ultra-RC BD. The patient had depressive episodes with anergy and marked social withdrawal interspersed with hypomanic episodes with elevated mood, tachypsychia, and increased energy levels, each lasting from a few days to 2 weeks.…”
Section: Discussionmentioning
confidence: 97%
“…In the next step, data were extracted from the SZ patients’ medical records through the use of chart files in the form of an electronic table with the following data: age, sex, duration of SZ treatment, number of previous ineffective pharmacotherapy trials before introducing lurasidone augmentation of clozapine, antipsychotic drug used in combination with clozapine before lurasidone, clozapine dose, somatic comorbidities, substance abuse, psychiatric and nonpsychiatric drugs (and their doses) concomitantly used by the patients, initial and final lurasidone doses, duration of lurasidone augmentation of clozapine treatment, and observable effects of the use of this combination. We evaluated the data for the presence of the following symptoms and conditions: residual positive symptoms, exacerbation of positive symptoms, negative symptoms, anxiety symptoms, suicidal ideations, cognitive impairment, sexual dysfunctions, hyperprolactinemia, increased appetite and weight/obesity, and glucose intolerance (features such as metabolic disorders, hyperprolactinemia, and cognitive dysfunctions were selected due to the reported favorable profile of the lurasidone effect on metabolic parameters and cognitive functions and a possible risk of hyperprolactinemia [ 27 , 28 ]). Moreover, we retrospectively assessed the Clinical Global Impression—Severity (CGI-S) scores before treatment initiation, at months 1, 2, and 3 and then every three months.…”
Section: Methodsmentioning
confidence: 99%
“…I read with great interest the two articles on lurasidone published in this journal. Siwek and Gorostowicz [2] reported that lurasidone is effective in a patient with rapid cycling bipolar disorder who are obese or have metabolic abnormalities. Reynolds et al [3] showed that lurasidone suppressed olanzapine-induced weight gain in rats.…”
Section: To the Editormentioning
confidence: 99%
“…Both psychiatric symptoms and blood glucose levels are controlled by the central nervous system. Because lurasidone has few adverse metabolic effects, as reported by Siwek and Gorostowicz [ 2 ] and Reynolds et al . [ 3 ] in this Journal, it is possible to examine the relationship between psychiatric symptoms and blood glucose levels in a naturalistic manner.…”
Section: To the Editormentioning
confidence: 99%